John - Brant, Jo-Ann A., 1956- (Grand Rapids, Mich. : Baker Academic, 2011)
In this addition to the well-received Paideia series, Jo-Ann Brant examines cultural context and theological meaning in John. Paideia commentaries explore how New Testament texts form Christian readers by attending to the ancient narrative and rhetorical strategies the text employs, showing how the text shapes theological convictions and moral habits, commenting on the final, canonical form of each New Testament book, focusing on the cultural, literary, and theological settings of the text, and making judicious use of maps, photos, and sidebars in a reader-friendly format. This commentary, like each in the projected eighteen-volume series, proceeds by sense units rather than word-by-word or verse-by-verse. (Amazon)
Part I. In the beginning (John 1:1-2:12) -- Part II. Jesus's itinerant ministry (John 2:13-12:11) -- Part III. Jesus's triumphant hour (John 12:12-19:42) -- Part IV. Jesus's resurrection : endings and epilogues (John 20:1-21:25).
Includes bibliographical references (p. 291-303) and indexes.
Keywords: Bible. -- Commentaries